Entrepreneurial Resilience In MSMEs Food in Disaster-Prone areas in West Sumatra - Primadona; Emrizal (CV. AFDIFAL MAJU BERKAH, 2022)
This study resulted in the effect of social capital, entrepreneurial experience and knowledge on entrepreneurial resilience. West Sumatra is one of the disaster-prone areas in Indonesia, so it is necessary to examine whether social capital, entrepreneurial experience and knowledge have an influence on entrepreneurial resilience with the case of food SMEs. We need to do this research to find out whether in disaster areas social capital, experience and knowledge contribute to creating entrepreneurial resilience. This study used 384 samples of food SMEs spread over 5 disaster areas in West Sumatra. Data were collected using a questionnaire which was processed using the SPSS tool with the questionnaire measurement scale being the Likert scale. The unit of analysis is the owner of food SMEs in West Sumatra specifically in disaster areas. By collecting as many as 384 respondents it is believed to be representative because the number of food MSMEs is definitely not contained in any information because it is rapidly growing. The results of the study reveal that the variables of social capital, entrepreneurial experience and knowledge have an effect on entrepreneurial resilience by 43.4%, while the rest are influenced by other variables that have not been taken into account in this study. Further research can be done by including other variables such as business performance, or entrepreneurial orientation.